Inovasi Penanaman Nilai-Nilai Karakter Pendidikan Agama Islam pada Anak Usia Dini melalui Metode Permainan di Taman Kanak-Kanak - Suryaningtyas, Ariany Katrin; Afifah, Nur; Nursikin, Mukh (Lembaga Yasin AlSys, 2022)
This study aims to describe the innovation of planting character valuesof Islamic religious education through the game method. This study uses the type of action research (action research) while the data collection methods used are interviews, observation and documentation.The development of religious and moral intelligence innovations can be used to instill character values in the learning process of Islamic Religious Education, including: hijaiyah lettering games, arranging pictures of ablution sequences, prayer sequences puzzles. From the game, it is hoped that it can bring out the character values of good Islamic religious education in early childhood.